CO2 Transoral Microsurgery for Supraglottic Squamous Cell Carcinoma - Carta, Filippo; Mariani, Cinzia; Sambiagio, Giovanni B.; Chuchueva, Natalia; Lecis, Elisa; Gerosa, Clara; Puxeddu, Roberto (Frontiers in Oncology, 2018)
The present study analyzed functional and oncologic outcomes after different endoscopic transoral CO2 laser supraglottic laryngectomies for T1, T2 and selected T3 supraglottic carcinoma. This is a retrospective clinical study of 42 consecutive patients treated by the senior author and reviewed from November 2010 to September 2017. Surgical procedures were classified according to the European Laryngological Society. In addition to the standardized transoral supraglottic laryngectomies, we introduced a modified type IVb by sparing the inferior third of the arytenoid if not directly involved in the tumor. Swallowing was evaluated with the Swallowing Performance Status Scale reported by the Multinational Association of Supportive Care in Cancer/International Society of Oral Oncology. Survival probabilities were estimated using Kaplan-Meier curves. Two type I, 2 type IIa, 2 type IIb, 3 type IIIa, 12 type IIIb, 13 type IVa, 3 type modified IVb, and 5 type IVb supraglottic laryngectomies were performed. Twenty-one patients underwent primary neck dissection. The pathologic TNM classification (8th edition of the American Joint Committee on Cancer) was: 9 pT1cN0, 2 pT1N0, 1 pT1N1, 7 pT2cN0, 1 rypT2cN0, 9 pT2N0, 4 pT2N1, 2 ypT2N1, 2 pT3cN0, 2 rypT3cN0, 1 pT3N1 and 2 pT3N2b. Mean follow-up was 3.4 years. Five-year disease-specific survival, local-relapse-free survival, nodal-relapse-free survival, overall-laryngeal-preservation and overall survival were 93.1%, 90.5%, 83%, 90.7%, and 64.9%, respectively. Patients started oral feeding the day after surgery after type I, IIa and IIb resections (n=6), 3-4 days after surgery after type III-IVb modified resections (n=31), and 7 days after surgery after type 4b resections (n=5). Three months after surgery, patients without previous head and neck radiotherapy/open surgery who underwent type III, IVa, and modified IVb resections showed significantly better swallowing compared to patients who underwent standard type IVb resection: grade 4-6 impairment of swallowing in 8% and 66.7% of cases, respectively (p=0. 006072). Transoral CO2 laser supraglottic laryngectomy is an oncologic sound alternative to traditional open neck surgery and chemo-radiotherapy. Recovery of swallowing is significantly worsened after total resection of the arytenoid. Modified type IVb procedure leaving intact, when possible, the inferior third of the arytenoid and consequently the glottic competence, improves functional outcome.